Sociocultural influences on asthma self‐management in a multicultural society: A qualitative study amongst Malaysian adults. (27th August 2021) - Koh, Wen Ming; Abu Bakar, Ahmad Ihsan; Hussein, Norita; Pinnock, Hilary; Liew, Su May; Hanafi, Nik Sherina; Pang, Yong Kek; Ho, Bee Kiau; Mohamed Isa, Salbiah; Sheikh, Aziz; Khoo, Ee Ming
Abstract: Background: Supported self‐management improves asthma outcomes, but implementation requires adaptation to the local context. Barriers reported in Western cultures may not resonate in other cultural contexts. We explored the views, experiences and beliefs that influenced self‐management among adults with asthma in multicultural Malaysia. Methods: Adults with asthma were purposively recruited from an urban primary healthcare clinic for in‐depth interviews. Audio‐recordings were transcribed verbatim and analysed thematically. Results: We interviewed 24 adults. Four themes emerged: (1) Participants believed in the 'hot and cold' concept of illness either as an inherent hot/cold body constitution or the ambient temperature. Hence, participants tried to 'neutralize' body constitution or to 'warm up' the cold temperature that was believed to trigger acute attacks. (2) Participants managed asthma based on past experiences and personal health beliefs as they lacked formal information about asthma and its treatment. (3) Poor communication and variable advice from healthcare practitioners on how to manage their asthma contributed to poor self‐management skills. (4) Embarrassment about using inhalers in public and advice from family and friends resulted in a focus on nonpharmacological approaches to asthma self‐management practice. Conclusions: Asthma self‐management practices were learnt experientially and were strongly influenced by sociocultural beliefs and advice from family and friends. Effective self‐management needs to be tailored to cultural norms, personalized to the individuals' preferences and clinical needs, adapted to their level of health literacy and underpinned by patient–practitioner partnerships. Patient and Public Contributions: Patients contributed to data. Members of the public were involved in the discussion of the results.